2023
DOI: 10.3389/jpps.2023.11699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of dexmedetomidine nasal spray in the treatment of sleep disorders on the first night after undergoing maxillofacial surgery: a single-center double-blind randomized controlled study

Ye Wang,
Zibin Jin,
Wenli Xu
et al.

Abstract: Purpose: Dexmedetomidine exerts a sedative effect by promoting the sleep pathway endogenously and producing a state similar to N2 sleep. This study aimed to study the efficacy and safety of dexmedetomidine nasal spray in the treatment of postoperative sleep disturbance.Methods: This study enrolled 120 participants [men and women; age, 18–40 years; American Society of Anesthesiologists grade, I or II] who underwent maxillofacial surgery under general anesthesia through nasotracheal intubation. The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It was demonstrated that intranasal dexmedetomidine could improve postoperative sleep quality in patients with chronic insomnia, without increasing the incidence of adverse effects [26]. To be more specific, the use of dexmedetomidine prolonged N2 and N3 sleep duration and shortened average length of hospitalization [27]. The effectiveness of dexmedetomidine accounts for the high presence in our keywords map.…”
Section: Discussionmentioning
confidence: 76%
“…It was demonstrated that intranasal dexmedetomidine could improve postoperative sleep quality in patients with chronic insomnia, without increasing the incidence of adverse effects [26]. To be more specific, the use of dexmedetomidine prolonged N2 and N3 sleep duration and shortened average length of hospitalization [27]. The effectiveness of dexmedetomidine accounts for the high presence in our keywords map.…”
Section: Discussionmentioning
confidence: 76%